BRACHYTHERAPY RADIATION STENT FOR MUCOEPIDERMOID CARCINOMA– A CASE REPORT - Dr. Sanath Kumar Shetty; Dr. Basith Ali; Dr. Rajesh Shetty; Dr. Sayed Suhaim (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Direct application of radioactive sources to the cancerous site is known as brachytherapy, or BT. The target volume center receives high-dose radiation delivery using this approach, which is marked by a steep dose gradient while the surrounding healthy tissues are spared. A 30-year-old female patient reported to the Department of Prosthodontics with a lesion in the palatal region. The lesion presents as mucoepidermoid carcinoma of the hard palate. The patient was referred from the Department of Oncology for the provision of a radiation carrier stent for interstitial brachytherapy of the hard palate for conventional radiotherapy. A brachytherapy radiation stent was fabricated for the hard palate for focusing the radiation in the specific region of the lesion.